Smart City Infrastructure Management System Using IoT - Ramamoorthy, S; Kowsigan, M; Balasubramanie, P; Paul, P. John (Role of Edge Analytics in Sustainable Smart City Development, 2020)
The development of smart cities involves adoption of advanced Information and Communication Technologies (ICT) in the process of enhancing the performance of the urban services. The major objective of the smart city is to reduce the resource, energy consumptions and overall cost. The models also ensure that individual privacy and safety on the data today activities across the city. The Internet of Things (IoT) is the major enabling technology in the background of smart city development in the urban location. An efficient way of placing and integrating the smart intelligent sensors on the predominant locations of the city and capture the data for analysis and decision making process. The sensors embedded as a part of object which can sense and transmit the data to the reporting end. The centralized server with customized software can be able to analyze the data received from the intelligent servers to predict and initiate the real time actions accordingly [3].